The small-world and scale-free structure of an internet technological community. (29th December 2008) - Yan, Jie; Assimakopoulos, Dimitris
Two network topology models, 'small-world' and 'scale-free' networks, have been recently introduced by physicists and mathematicians, generating a growing interest from the natural and social scientists interested in the dynamics of networks and related communities. In this paper, we analyse the structure of the questioning and replying network in a very large internet technical community, China Software Development Net (CSDN). CSDN is the biggest Chinese language software technical forum, with over one million registered members by early 2006. Our findings indicate that the CSDN network presents both small-world and scale-free properties. The technology and knowledge management implications for this network structure are discussed with respect to the technical knowledge and innovation diffusion in large technological communities.